1979
DOI: 10.1172/jci109539
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Hemoglobin H Disease by Sickle Trait

Abstract: A B S T R A C T The rarity of hemoglobin (Hb) H disease in combination with sickle trait may be due in part to the absence ofactual Hb H in individuals who, nonetheless, have inherited the deletion of three a-globin genes. We describe here a boy with persistent microcytic, hypochromic anemia despite adequate iron stores, who exhibited splenomegaly with a normal reticulocyte count and only rare inclusions in circulating erythrocytes. Starch gel electrophoresis and isoelectric focusing at age 5 yr showed 21% Hb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…with the AS; --/-a genetic condition closely resembles the sixyear-old black-Chinese boy described by Matthay el a1 [17] Pi tetramers in the youngest red cells and not in the older cells isolated from the bottom layers is consistent with the known physico-chemical properties of these abnormal Hbs and may to some extent explain the difficulties in identifying these Hb variants in whole red cell lysates.…”
Section: Discussionsupporting
confidence: 69%
“…with the AS; --/-a genetic condition closely resembles the sixyear-old black-Chinese boy described by Matthay el a1 [17] Pi tetramers in the youngest red cells and not in the older cells isolated from the bottom layers is consistent with the known physico-chemical properties of these abnormal Hbs and may to some extent explain the difficulties in identifying these Hb variants in whole red cell lysates.…”
Section: Discussionsupporting
confidence: 69%
“…Matthay et al [23] have suggested that sickle cell trait may modify Hb H disease because the relatively low Hb A level reduces the availability of ␤ -chains to form Hb H.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, an unusual EE/Hb H interaction has been observed in a 34-year-old Thai woman 10 who had only 4% of Hb F without Hb Bart, and it has been suggested that the absence of Hb Bart might have been a result of diminished adult level of c-globin expression similar to the temporal decline of Hb F and Bart in an individual with Hb S and a single a-gene. 11 However, previous studies from Thailand demonstrated that Hb Bart in this syndrome could be detected even in the sixth decade of life, 3 and our observation of this ''cinactive'' EE/Hb H in two different age groups suggests that the chronological decreased c-expression seems unlikely. However, this may suggest that there is a different genetic background acting either in cis or in trans on the c-globin expression in these individuals that differentiates them from the majority of cases with EE/Hb H. Study of these unusual cases in greater detail may provide some insights in different genetic heterogeneity of the c-globin expression and persistent production of Hb F in our population.…”
Section: Discussionmentioning
confidence: 48%